Logistics cost determinants at CTRM Aero Composites Sdn Bhd / Mohd Azlan Ahmad - Ahmad, Mohd Azlan (Faculty of Business and Management, 2007)
In year 2006 Composites Technology Research Malaysia Aero Composites Sdn Bhd exhibited 20% of the company expenditure comes from logistics. Among the problems faced by the company this study was conducted to examine the logistics costs influenced at Composites Technology Research Malaysia Aero Composites Sdn Bhd. The objective of this study was to identify the major factors that affect logistical costs of Composites Technology Research Malaysia Aero Composites Sdn. Bhd. To meet the objectives, researcher used two methods that is trend analysis and regression analysis. For trend analysis, the researcher wanted to figure out the fluctuation to the logistics costs. In addition for the major factors that affected the logistics costs, researcher used regression analysis in order to understand which factors that influence logistics costs more. This study found out the trend shows that logistics costs at CTRM AC Sdn Bhd do have a variability which consists of the increased and declined of the slope. In other hand, by using regression analysis it showed the variables significantly towards the logistics costs. Among the eleven variables only four were significant which were the Gross Domestic Product for Malaysia, the United States and the United Kingdoms and the Exchange Rate for the United Kingdoms.